Related Party Transactions and Accrual Earnings Management: The Role of Organizational Capital as a Moderator - Rossa, Elia; Ali, Hapzi; Sudiantini, Dian (Dinasti Publisher, 2024)
This study aims to test and analyze the effect of related party transactions on accrual earnings management which is moderated by organizational capital. This study uses manufacturing companies listed on the Indonesian Stock Exchange (BEI) in 2018-2021 using a purposive sampling method. A panel data approach was used to test the hypotheses of this study. The results of this study found that related party transactions had a positive and significant effect on accrual earnings management, while organizational capital cannot strengthen the effect of related party transactions on accrual earnings management. This study has important implications for the development of agency theory. This study shows that agency theory has an important role in creating information asymmetry between shareholders and company management. Information asymmetry triggers managers' actions to manage earnings on an accrual basis through the use of related party transactions. The aim is to improve company management performance, so that managers' motivation to obtain bonuses can be achieved.